PENGUATAN EKONOMI MASYARAKAT MELALUI PLATFORM INDUSTRI KREATIF - Etty Puji Lestari; Tri Kurniawati Retnaningsih; Erlambang Budi Darmanto; Richmond Faithful; M. Farhan Al Ja'fary (LPPM Universitas Bina Bangsa, 2024)
Creative industries play an essential role in a country's economy, but their development has yet to be maximized; one is in Bojongsari District, Depok. Many homemakers set aside and fill their activities with unproductive things so that no economic contribution is generated. Based on this situation, activities aimed to empower homemakers and provide them with creative industries are expected to increase their family income. The Universitas Terbuka Community Service Program, in collaboration with Craft Studio Panorama/CSP 11 Depok, tries to apply a new paradigm in community service activities that is problem-solving, comprehensive, thorough, and sustainable with a goal that is not single through the macrame crafting industry, fashion, and bags. The community service results show that the community appreciates this community service activity. This community service is proven to provide additional income and also empowers local communities to be more productive